Gait Deterioration in Adolescents with Dravet Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at the University of Melbourne, Australia studied prospectively changes in gait by age in patients with Dravet syndrome. Of 26 patients aged 2 to 34 years, 15 were male and 11 female, mean age 11.6 years; 23 had SCN1A mutations.